Distribution Characteristics of 29 Antibiotics in Groundwater in Harbin - MA Jian-sheng; WANG Zhuo; ZHANG Ze-yu; LIU Qiang; LI Li-jun (Yankuang ceshi, 2021)
BACKGROUND At present, the supervision of antibiotic abuse and its research is being strengthened. In recent years, antibiotics have been detected in varying degrees in water in central China. This reinforces the concern of the pollution of antibiotics in surface and groundwater. OBJECTIVES To investigate the distribution characteristics of 29 antibiotics in groundwater in Harbin. METHODS A total of 26 groups of groundwater samples were collected in Harbin, and the sampling scope included habitation and production areas such as densely populated, industrial production, agricultural districts and animal husbandry. The ultra-performance liquid chromatography-triple quadrupole mass spectrometry method was used to analyze 29 kinds of antibiotics covering six types, including sulfonamides, quinolones, macrolides, β-lactams, tetracyclines, and lincosamides. RESULTS Antibiotics in the groundwater of Harbin were mainly composed of sulfonamides, quinolones, macrolides and tetracyclines and the detection rates were 61.5%, 46.2%, 42.3% and 38.5%, respectively. The content of antibiotics detected ranged from 0.02 to 681ng/L, and the highest contents of sulfathiazole, sulfadiazine, and lincomycin were more than 100ng/L. The average content of quinolones was low compared with some domestic and international areas (such as Beijing, Tianjin, and Barcelona). Sampling sites with higher antibiotic levels were mainly found in the central, southern and eastern regions of the city. These areas are also relatively densely populated and are generally distributed around pharmaceutical factories, urban sewage outlets, and poultry and livestock farms. CONCLUSIONS The distribution characteristics of antibiotics in groundwater in Harbin are strongly related to the impact of human production and living activities.